Topography and scale in a community-driven maternal and child health program in Eastern Indonesia (Medicine Anthropology Theory, 2020)
In 2007, the Indonesian government introduced Generasi, a community-driven development program to address village priorities such as reducing poverty, maternal mortality, and child mortality. When describing Generasi’s biggest challenges, program facilitators on the eastern Indonesian island of Flores used a geographic vocabulary of fields (medan, lapangan) and topography (topografi) that evokes the demands of supervising Generasi’s implementation across dozens of mountain villages with poor infrastructure. But their geographic language also extends metaphorically to the enduring problems of scale and governance. I analyze these discourses of topography and field in relation to the changing therapeutic landscape of maternal and child health services in the Manggarai highlands of western Flores, then follow Generasi’s scalar scaffolding from the meetings and clinics in villages, to the technocratic policy work in Jakarta, and to the academic spaces of Auckland and Cambridge.